2023
DOI: 10.1111/geb.13751
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of bacterial generalists and specialists in lakes and reservoirs along a latitudinal gradient

Jun Zuo,
Lemian Liu,
Peng Xiao
et al.

Abstract: AimThe geographical distribution of bacteria is an important, but poorly understood, topic in microbial ecology. A major question is how broadly distributed generalist taxa, and limitedly distributed specialist taxa, vary across a latitudinal gradient in freshwater ecosystems. We predict that: (a) generalists and specialists exhibit latitudinal diversity gradient with different patterns; (b) their community assemblies are mainly driven by stochastic processes; and (c) generalists coexist through niche differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 117 publications
2
5
1
Order By: Relevance
“…Moreover, as a widely studied alpha diversity pattern, 28 species diversity decreases with increasing latitude. 29 However, in the present study, the microbial diversity of the lakes did not increase from the upstream to downstream of watershed. Although the lake was connected with the rivers, the independence between the lakes was strong, and the lakes in upstream can hardly interact hydrologically with the lakes downstream.…”
Section: Discussioncontrasting
confidence: 68%
“…Moreover, as a widely studied alpha diversity pattern, 28 species diversity decreases with increasing latitude. 29 However, in the present study, the microbial diversity of the lakes did not increase from the upstream to downstream of watershed. Although the lake was connected with the rivers, the independence between the lakes was strong, and the lakes in upstream can hardly interact hydrologically with the lakes downstream.…”
Section: Discussioncontrasting
confidence: 68%
“…This contrast may point to a fundamental difference in host filtering compared to free-living bacterial community assembly. However, these systems, like ours (Figure 2), showed that generalist bacterial lineages are more geographically structured than specialists (Liao et al 2016;Hu et al 2019;Luo et al 2019;Zuo et al 2023).…”
Section: Discussionsupporting
confidence: 55%
“…This difference is likely driven by the absence of highly prevalent and host generalist Proteobacteria ASVs in high diversity host communities (Figure 2, Table S2), contradicting our hypothesis that high host diversity would drive ASVs to become either highly specialist, or highly generalist. Our data show patterns that directly contrast with free-living bacteria assemblages, in which generalist microbes are more diverse at southern latitudes (Zuo et al 2023). This contrast may point to a fundamental difference in host filtering compared to free-living bacterial community assembly.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For instance, the community assembly of generalists and specialists in the sedimentary habitats of Lake Tibetan was been found to be dominated by stochastic processes [30]. However, study [31] pointed out that the community assembly of specialists in upland lakes is controlled only by deterministic processes, which is consistent with the results of studies on generalists and specialists in lakes and reservoirs at different latitudes in eastern China [32].…”
Section: Introductionsupporting
confidence: 69%